2017
DOI: 10.1016/j.vascn.2016.12.003
|View full text |Cite
|
Sign up to set email alerts
|

A new paradigm for drug-induced torsadogenic risk assessment using human iPS cell-derived cardiomyocytes

Abstract: These results indicate that our torsadogenic risk assessment is reliable and has a potential to replace the hERG assay for torsadogenic risk prediction, however, this system needs to be improved for the accurate of prediction of clinical TdP risk. Here, we propose a novel drug induced torsadogenic risk categorising system using hiPSC-CMs and the MEA system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
99
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 156 publications
(111 citation statements)
references
References 61 publications
10
99
1
Order By: Relevance
“…1 (B)). Recently, it was demonstrated that drugs could be categorized into three TdP risks based on the effect of the drugs on extracellular field potential with MEA (Ando et al, 2017). According to that report, astemizole and bepridil were classified as intermediate risk, which was slightly different from our study.…”
Section: Resultscontrasting
confidence: 93%
See 1 more Smart Citation
“…1 (B)). Recently, it was demonstrated that drugs could be categorized into three TdP risks based on the effect of the drugs on extracellular field potential with MEA (Ando et al, 2017). According to that report, astemizole and bepridil were classified as intermediate risk, which was slightly different from our study.…”
Section: Resultscontrasting
confidence: 93%
“…These assays detect changes in electrical activity of cardiomyocytes upon drug treatment for a short period (several minutes to several hours). The Consortium for Safety Assessment using Human iPS Cells (CSAHi) initiated an effort to establish standard protocols by MEA systems for risk assessment of arrhythmia and QT prolongation using various reference drugs (Ando et al, 2017;Asakura et al, 2015;Nozaki et al, 2016Nozaki et al, , 2017Yamamoto et al, 2016). In those experimental processes, Nozaki et al (2017) investigated gene expression profiles using hiPS-CMs that were cultured in three different facilities to assess the equivalency of the data among laboratories; there was no difference among the gene expression profiles in the three facilities.…”
Section: Introductionmentioning
confidence: 99%
“…TdP, associated with the substance [24,25]. Few studies show the effect of arrhythmogenic drugs on arrhythmic beating, changes in beat rate [2] and FPD [14] using monolayers of human iPSC-derived cardiomyocytes (iCell®). Shaheen et al ArcLight for evaluation of conduction slowing and APD prolongation under chemical compounds [15].…”
Section: Discussionmentioning
confidence: 99%
“…Cell chips in which cells are arranged on a microarray have recently been developed. Assays using such chips can simultaneously evaluate multiple items using a small amount of cells and samples, and are useful for rapid and easy high‐throughput screening (Ando et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…amount of cells and samples, and are useful for rapid and easy highthroughput screening (Ando et al, 2017).…”
mentioning
confidence: 99%